Review of Dengue Deaths in Bangladesh: An Interim Analysis of the 2023 Outbreak (Bangladesh Journal of Medicine, 2024)
Background: Dengue fever is one of the most prevalent mosquito-borne diseases and is categorized as a neglected tropical disease (NTD) by the World Health Organization (WHO). Last year, Bangladesh witnessed an unprecedented dengue outbreak, claiming a record-breaking 1705 lives and posing a significant public health concern. This presents the preliminary analysis of the demographics and clinical features associated with dengue-related fatalities in 2023. Methods: This study presents a retrospective analysis of 94 dengue death cases, which were collected from 15 different hospitals in Bangladesh between January 1, 2023, to December 31, 2023. The cases were classified based on the patient's age as children (age 60 years). The study aimed to investigate the demographic and clinical characteristics of the patients and also explores adherence to national guidelines for IV fluid management. Results: The data reveals that among the patients, 11.8% were children, 65.6% were adults, and 22.6% were elderly. Furthermore, 52.7% of the patients were male, while 47.3% were female. Comorbidities such as diabetes mellitus and hypertension were prevalent among the patients. The median duration between disease onset and hospitalization was 3.0 (IQR: 2.0 - 5.0) days, and the median duration of hospital stay was 1.0 (IQR: 0.61 – 2.0) days. Expanded Dengue Syndrome (29.8%) was the most common diagnosis at admission, followed by Dengue Shock Syndrome (26.6%), Dengue Hemorrhagic Fever (DHF) (17.0%), and Dengue Fever (DF) (14.9%). The study also revealed that only 35.1% of the patients received IV fluid treatment according to the national guideline, 47.9% did not, and no relevant record was found for the remaining 17% of cases. The patient follow-up was according to the guideline for 12.8% of patients, while 38.3% were not, and 48.9% had no record. Moreover, it was found that patients who received IV fluid treatment according to the guideline survived significantly longer than those who did not, with a mean difference of 1.26 days (p